2015
DOI: 10.1556/018.66.2015.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and biodiversity of endophytic phosphorus- and potassium-solubilizing bacteria in Moso Bamboo (Phyllostachys edulis)

Abstract: Endophytic phosphorus-and potassium-solubilizing bacteria were screened from the root, rhizome, stem, and leaves of Moso Bamboo, and their diversity was analyzed using their 16S rDNA sequences. Twenty endophytic phosphorus and potassium-solubilizing bacteria were screened from 82 bamboo plants, among which the CT-B09-2, WYS-A01-1 and JL-B06 had higher activities in decomposing organophosphates. The three species showed a decomposition diameter/colony diameter (D/d) of 5.05, 4.19 and 2.95, respectively, and a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 19 publications
(11 reference statements)
1
14
0
Order By: Relevance
“…subtilis EPP65, B. cereus EPP5, and B. cereus EPP71 have been reported as antagonistic endophytes in pearl millet host. These results are in conformity with previous published research findings of Ramesh et al [83], Yuan et al [84], and Nair and Padmavathy [85] that highlighted the K and Zn solubilizing potential of endophytic Bacillus strains. There might be a possibility that seed soaking with endophytic strain of Bacillus can result in rapid introduction, penetration, and colonization of internal sections of root radicals, as observed by Algam et al [86].…”
Section: Discussionsupporting
confidence: 93%
“…subtilis EPP65, B. cereus EPP5, and B. cereus EPP71 have been reported as antagonistic endophytes in pearl millet host. These results are in conformity with previous published research findings of Ramesh et al [83], Yuan et al [84], and Nair and Padmavathy [85] that highlighted the K and Zn solubilizing potential of endophytic Bacillus strains. There might be a possibility that seed soaking with endophytic strain of Bacillus can result in rapid introduction, penetration, and colonization of internal sections of root radicals, as observed by Algam et al [86].…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that Bacillus and Pseudomonas are the most abundant strains of KSB isolated from the crop rhizosphere [20]. Inoculation with Enterobacter bacterial strains, which had strong activities for solubilizing potassium, was found to facilitate the mobilization of potassium efficiently in plants, when feldspar was added to the soil [46]. Interestingly, 25 Enterobacter isolates were found in S2 and S3, in comparison with one isolate in S1, meaning that the growth of Enterobacter is affected by the utilization of fertilizer.…”
Section: Discussionmentioning
confidence: 99%
“…Research on various plant species, including Arabidopsis thaliana (eudicot) ( Bai et al, 2015 ), rice ( Zhang et al, 2019 ; Kim and Lee, 2020 ), sorghum ( Emmett et al, 2017 ) (monocot) and Cycas panzhihuaensis (gymnosperm) ( Zheng and Gong, 2019 ) has revealed that plant compartments, environmental conditions and host phylogeny are the most predominant factors influencing plant-microbial consortia ( Bouffaud et al, 2014 ). Diverse microbes have been found in bamboo leaves, rhizomes, roots, and seeds ( Shen et al, 2014 ; Liu et al, 2017 ) based on culture-dependent and independent methods ( Yuan et al, 2015a ; Debnath et al, 2018 ), some of which were endophytic phosphorus- and potassium-solubilizing bacteria ( Yuan et al, 2015b ; Yuan et al, 2018 ). The photosynthetic rate, transpiration rate, and stomatal conductance in Phyllostachys edulis treated with these growth-promoting bacteria were all higher than in the control groups ( Yuan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A small amount of research concerning bamboos and their associated microbes have been conducted previously, revealing that different bamboo species are colonized by various endophytes ( Han et al, 2009 ; Xu et al, 2014 ), some of which were growth-promoting bacteria capable of dissolving phosphorus and potassium as well as fixing nitrogen ( Yuan et al, 2015b , 2018 ). However, these researches were largely culture-dependent and restricted to single or few species, likely to underestimate the exact diversity and composition of bamboo endophytes.…”
Section: Introductionmentioning
confidence: 99%